Compliance with the Standards of the Diplomatic Protocol and Etiquette as a Component of State Policy at the Present Stage - Ryeznikov, Valerij; Koval, Yulia (Pressing Problems of Public Administration, 2024)
The paper presents the author’s analysis and view on topical issues, but rather little covered, of diplomatic protocol and etiquette and its use at the present stage. The purpose of the article is to determine the specifics of the influence of compliance with the norms of diplomatic protocol and etiquette on the image of the state and its official representatives, as modern actors of diplomatic and political relations between countries and governments. The historical stages of development of diplomatic protocol and etiquette are systematized and highlighted. The paper presents a comparative analysis of compliance with the rules of diplomatic protocol, etiquette and ceremony, as well as cases of deviation from the traditional and classical norms of compliance with the state protocol at the present stage. A SWOT-analysis of compliance with the rules of diplomatic protocol and etiquette by the current President of Ukraine is presented, where cognitive aspects as political components of the head of state are presented. As a result of the analysis of the role and importance of diplomatic protocol and etiquette in international relations, it was established that certain types of diplomatic communication influence the observance of certain norms of behavior in special conditions. It has been found that under the influence of the globalization and democratization processes, diplomacy goes from classic closed to public open, and this affects the behavior of heads of state, politicians and statesmen, as well as the means of forming their own image.